Association of Fatigue and Outcomes in Advanced Cancer: An Analysis of Four SWOG Treatment Trials. Issue 8 (August 2021) - Mo, Julia; Darke, Amy K.; Guthrie, Katherine A.; Sloan, Jeff A.; Unger, Joseph M.; Hershman, Dawn L.; O'Rourke, Mark; Bakitas, Marie; Krouse, Robert S.
Abstract : PURPOSE: Patient-reported outcomes may be associated with cancer outcomes. We evaluated clinically significant fatigue (CSF), overall survival, adverse events (AEs), and quality of life (QOL) during cancer treatment. METHODS: We compared outcomes in four phase II or III chemotherapy trials, two advanced non–small-cell lung cancer and two advanced hormone-refractory prostate cancer, with or without baseline CSF. CSF was defined as a rating of two or greater on the Functional Assessment of Cancer Therapy fatigue question or a European Organization for Research and Treatment of Cancer Quality of Life Questionnaire—Core 30 fatigue symptom score of 50% or greater. Survival was compared according to CSF using Kaplan-Meier estimates and Cox regression models. Differences in AE rates by CSF were assessed via chi-squared tests, and QOL changes from baseline to 3 months via linear regression. RESULTS: Of 1, 994 participants, 1, 907 (median age 69 years, range: 32-91) had complete baseline QOL survey data, with 52% reporting CSF at baseline. For the two hormone-refractory prostate cancer studies, baseline CSF was associated with higher mortality rates, with adjusted hazard ratios of (95% CI, P value) 1.32 (1.13 to 1.55, P < .001) and 1.31 (1.02 to 1.67, P = .03) and with increased incidence of grade 3-5 constitutional (16.5% v 9.4%, P = .002; 13.9% v 6.3%, P = .002) and neurologic (11.7% v 6.1%, P = .006; 9.0% v 3.9%, P = .01) AEs, respectively. Baseline CSF was associated with a higher mortality rate in one non–small-cell lung cancer study: hazard ratio 1.44 and 1.04 to 2.00, P = .03. CONCLUSION: Oncology trial participants with baseline CSF had poorer survival and experienced more AEs than participants without CSF. This indicates fatigue as an important baseline prognostic factor in oncology treatment trials.